Does ugly art foster creative thinking - Morone, Valeria (2022)
This thesis aims to investigate the influence that visual art exerts on creative thinking. Specifically, this research analyzes the different levels of creativity and curiosity triggered by the observation of a commonly considered “beautiful” visual artwork -complying to rules and proportions, logical, and with technical skills; versus those caused by the view of an “ugly” (or aesthetically unpleasing) work of art –thus abstract, unskilled, disturbing, and with childish features. An experiment was conducted to test the predictions with data analysis including independent samplet tests and ANCOVA. The experiment showed that the level of creativity was not influenced by the exposure to “ugly art” versus “beautiful art”, however, higher levels of curiosity were triggered by exposure to “ugly art”. Finally, managerial implications are discussed.